The effect of mild preservation treatments on the invasiveness of different Listeria monocytogenes strains on Greenshell™ mussels. (January 2017) - Stollewerk, Katharina; Cruz, Cristina D.; Fletcher, Graham; Garriga, Margarita; Jofré, Anna
Abstract: High pressure processing (HPP) and thermal treatments are food preservation technologies used by the food industry to inactivate Listeria monocytogenes . However, the safe shelf-life of treated products could be compromised by the presence and/or recovery of surviving bacteria. The aim of the present study was to evaluate the effect of these technologies on the invasion capacity of L. monocytogenes . Eleven L. monocytogenes strains (serovars 1/2a, 1/2b, 1/2c and 4b) isolated from food processing plants and food products were grown in culture media, associated with Greenshell™ mussel surfaces and subjected (or not) to HPP (350 MPa, 2 min) or mild heating (MH, 55 °C, 10 min). The invasiveness of the strains was compared immediately after processing and after 14 days of storage at 8 °C using human intestinal epithelial Caco-2 cells. All strains on mussels had decreased invasion capacity compared with those coming directly from culture media. Invasiveness of L. monocytogenes also decreased immediately after pressurization but returned to the rate in untreated samples after 14 days of refrigerated storage. In contrast, MH did not affect invasion capacity, and treated samples showed the same rates as non-MH treated ones. Lineage I strains were more invasive than lineage II strains after both mild processing treatments. Based on these results, the risk of L. monocytogenes infection by the consumption of treated mussels will not be increased, as the invasiveness of possible survivors is not increased. Highlights: Listeria monocytogenes had reduced in vitro virulence when associated with Greenshell™ mussels. Mild heat did not affect invasion capacity of L. monocytogenes. High pressure processing temporally reduced L. monocytogenes invasiveness. Lineage I L. monocytogenes strains were more invasive than lineage II strains.